Managing a Conflict - Johannes Schneider; Benjamin Balzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study the optimal design of alternative dispute resolution (ADR) mechanisms by a third-party mediator. ADR takes place before two litigants face each other in court. Litigation is a legal contest with players who are privately informed about the cost of collecting admissible evidence. Players update their beliefs after the mediation process, but before they decide on evidence collection. Different from standard mechanism design problems, the belief-system post-ADR is important for the outcome of the continuation game: within litigation, choice variables are strategic complements and the evidence supplied is driven by the belief system. There is an incentive for parties to misreport in ADR to profit from this deviation in litigation should ADR fail to resolve the conflict. We show that optimal ADR has to break down on-path in some cases to screen the players with respect to their costs. Furthermore, ADR induces truthful reporting by creating post-breakdown beliefs which are independent of own type-reports during ADR. To reduce inefficiency vis-à-vis symmetric litigation, optimal ADR induces asymmetric breakdown beliefs even for ex-ante symmetric types to increase the settlement rate compared to symmetric mechanisms. Independent of the set of parameters, ADR achieves settlement for the majority of cases.
Keywords: D82; D74; K41; 330